QUANTITATIVE STUDIES OF SULFONAMIDE RESISTANCE - Kirby, William M. M. (The Rockefeller University Press, 1943)
1. In vitro experiments were performed with E. coli, using a method designed for the quantitative study of various aspects of sulfonamide resistance. 2. Resistance was found to be a gradually developing process, and was demonstrated for all four drugs tested, sulfanilamide, sulfapyridine, sulfathiazole, and sulfadiazine. 3. It was shown that the degree of resistance developed was correlated with the bacteriostatic potency of the sulfonamides, and that organisms resistant to certain bacteriostatic concentrations of one sulfonamide were equally resistant to similar bacteriostatic concentrations of the other sulfonamides. 4. These observations were interpreted as indicating that the development of sulfonamide resistance represents an interaction between the organisms and the one common structural unit of all the sulfonamides, namely, the p-amino nucleus. It is also suggested that this interaction may involve the same enzyme system (or systems) as those concerned in the antagonism of the sulfonamides by para-aminobenzoic acid. 5. The relation of these findings to the broader aspects of sulfonamide resistance is discussed, and it is postulated that, despite reports to the contrary, all organisms susceptible to the bacteriostatic action of the sulfonamides are capable of becoming resistant to all of the sulfonamides.